Drugs, the brain, and behavior : the pharmacology of drug use disorders - Brick, John, 1950-; Erickson, Carlton K. (New York : Routledge, 2013)
"Drugs, the Brain, and Behavior uses a balance of instruction, illustrations, and tables and formulas that will give you a broad, lasting introduction to this intriguing subject. Whether you're a nurse, chemical dependency counselor, psychologist, or clinician, this book will be a quick reference guide long after the first reading"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Drugs of abuse -- Physiological effect; Neuropharmacology; Neurophysiology; Electronic books